Electron microscopy of model systems - Meuller-Reichert, Thomas (Burlington, MA Academic Press is an imprint of Elsevier, 2010)
The volume covers the preparation and analysis of model systems for biological electron microscopy. The volume has chapters about prokaryotic as well as eukaryotic systems that are used as so-called model organisms in modern cell biology. These systems include the most popular systems, such as budding and fission yeast, the roundworm C. elegans, the fly Drosophila, zebrafish, mouse, and Arabidopsis, but also organisms that are less frequently used in cell biology, such as Chlamydomonas, Dictyostelium, Trypanosoma, faltworms, Axolotl and others. In addition, tissues and tissue culture systems are also covered. These systems are used for very diverse areas of cell biology, such as cell division, abscission, intracellular transport, cytoskeletal organization, tissue regeneration and others. Moreover, this issue presents the currently most important methods for the preparation of biological specimens. This volume, however, is not a classic EM methods book. The methods are not the main focus of this issue. The main goal here is to cover the methods in the context of the specific requirements of specimen preparation for each model organism or systems. This will be the first compendium covering the various aspects of sample preparation of very diverse biological systems.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Electron microscopy; Biological models; Electronic books